2009
DOI: 10.3892/mmr_00000209
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 and CYP1B1 polymorphisms as modifying factors in patients with pneumoconiosis and occupationally related tumours: A pilot study

Abstract: Abstract. CYP1A1 and CYP1B1 are involved in the metabolism of carcinogens. The effect of CYP1A1 and CYP1B1 polymorphisms as genetic modifiers of risk was investigated in individuals with asbestos, silica dust or ionizing radiationinduced occupational tumours compared to exposed non-cancer subjects suffering from pneumoconiosis, particularly in relation to tobacco smoking. CYP1A1 T6235C, CYP1A1 A4889G and CYP1B1 codon 432 polymorphisms were determined by realtime Pcr analysis in patients with asbestos-related l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Eight studies were population-based and one was hospital-based and the LC cases were histologically confirmed or cytologically confirmed in six of the eligible studies. All studies were in agreement with HWE of the genotype distribution of the controls, except for the study by Schneider et al [17], in which the HWE was unknown because it only provided the number of cases and controls for the Leu/Leu and Leu/ Val ? Val/Val genotypes.…”
Section: Study Characteristicsmentioning
confidence: 56%
See 3 more Smart Citations
“…Eight studies were population-based and one was hospital-based and the LC cases were histologically confirmed or cytologically confirmed in six of the eligible studies. All studies were in agreement with HWE of the genotype distribution of the controls, except for the study by Schneider et al [17], in which the HWE was unknown because it only provided the number of cases and controls for the Leu/Leu and Leu/ Val ? Val/Val genotypes.…”
Section: Study Characteristicsmentioning
confidence: 56%
“…There are two studies demonstrating a significantly increased risk of LC overall for carriers of the minor allele of CYP1B1 SNP rs1056836 among women and black ever-smoking women by Timofeeva et al [14] and Cote et al [15], respectively. However, other studies have failed to find any appreciable correlation between the CYP1B1 Leu432Val polymorphism and LC risk [16][17][18][19][20][21][22]. Moreover, two meta-analyses have investigated the same hypothesis [23,24], quite similar in methods, but the results do not appear to be the same.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A number of studies have compared past asbestos exposure and genetic polymorphisms using either candidate genes approaches (Betti et al, 2017;Borelli, Moura, Trevisan, & Crovella, 2015;Christiani, 2000;Crovella et al, 2016;Dianzani et al, 2006;Gemignani et al, 2009;Girardelli et al, 2012;Hirvonen et al, 1996;Landi et al, 2007;London et al, 1995;Murakami et al, 2012;Neri et al, 2008;Schabath et al, 2002;Schneider & Bernges, 2009;Tunesi et al, 2015;Wang, Neuberg, & Christiani, 2004) or whole-genome association studies for both MPM and LC (Cadby et al, 2013;Kettunen et al, 2017;Matullo et al, 2013;Wei et al, 2012). While low- (Cadby et al, 2013;Matullo et al, 2013) and high-risk (Betti et al, 2017;Ohar et al, 2016) genetic factors for MPM have been reported, even defining germline variants in BAP1 tumor suppressor gene as high-risk factor (Ohar et al, 2016), the impact individual genetic variations have on asbestos-related lung cancer risk is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%